Nas pegadas de um santo negro: a expressão feminina nos festejos de São Benedito na Praça Quatorze de Janeiro em Manaus, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This study deals with an analysis of the families living in Quilombo do Barranco de São Benedito and assumes the purpose of identifying a matriarchal structure present in quilombola families, organizers of the festivities of Saint Benedito. These festivities are present in this urban community located in the neighborhood of Praça Quatorze de Janeiro for more than a century, as a family tradition. This research takes an interdisciplinary perspective of dialogue with Anthropology, Sociology and History, based on the category of gender relations under the nexus of matriarchy. The matriarchy is taken in this thesis as a conceptual fragment, based on social practices of leadership and leadership exercised by women in the framework of the celebrations of Saint Benedito in Praça Quatorze de Janeiro, in Manaus, Amazonas. The field work is carried out under the contribution of qualitative approaches without exclusion of quantitative aspects, using ethnography method. One of the many verified results was the fact that the feminine is the guiding principle of society life in Quilombo do Barranco, and women are responsible for maintaining the culture in the community and for the continuity of the celebrations of Saint Benedito throughout historical time, resisting for more than a century. Women are the custodians and guardians of afrodescendant resistance culture within the only urban quilombo in Manaus. The religious tradition of the celebration of the black saint is maintained by women, based on matriarchal leadership, although it is not a system, but rather focuses and flaps of what the thesis concludes that is a matriarchy.
Keywords: Relações de Gênero; Resistência Cultural; Quilombo do Barranco de São Benedito; Protagonismo Feminino; CIÊNCIAS HUMANAS